2023
DOI: 10.1038/s41598-023-42341-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of plasma lipid abnormalities and associated risk factors among Iranian adults based on the findings from STEPs survey 2021

Javad Khanali,
Erfan Ghasemi,
Mohammad-Mahdi Rashidi
et al.

Abstract: The study aimed to estimate the prevalence of lipid abnormalities in Iranian adults by demographic characterization, geographical distribution, and associated risk factors using national and sub-national representative samples of the STEPs 2021 survey in Iran. In this population-based household survey, a total of 18,119 individuals aged over 25 years provided blood samples for biochemical analysis. Dyslipidemia was defined by the presence of at least one of the lipid abnormalities of hypertriglyceridemia (≥ 15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The WHO STEPS national survey results in 2021 concluded that 81.0% of the Iranian population (aged ≥ 25 years) had dyslipidemia. 8 Their finding indicated that low HDL-C (68.4%) was the most prevalent lipid abnormality, followed by hypertriglyceridemia (39.7%), hypercholesterolemia (21.2%), and high LDL-C (16.4%). Meanwhile, a meta-analysis of population-based studies from 1994 to 2015 estimated the prevalence of hypercholesterolemia at 42%, high LDL-C at 40%, and low HDL-C at 42%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The WHO STEPS national survey results in 2021 concluded that 81.0% of the Iranian population (aged ≥ 25 years) had dyslipidemia. 8 Their finding indicated that low HDL-C (68.4%) was the most prevalent lipid abnormality, followed by hypertriglyceridemia (39.7%), hypercholesterolemia (21.2%), and high LDL-C (16.4%). Meanwhile, a meta-analysis of population-based studies from 1994 to 2015 estimated the prevalence of hypercholesterolemia at 42%, high LDL-C at 40%, and low HDL-C at 42%.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Therefore, Tehran has a higher prevalence of dyslipidemia which can be possibly attributed to air pollution, a sedentary lifestyle, and unhealthy dietary habits compared to less populated provinces such as Golestan (68.5%), Kerman (74.1%), Mazandaran (76.6%), and Semnan (76.8%). 8 However, more studies are warranted to find evidence between the following risk factors and dyslipidemia. 22 , 23 A previous study has demonstrated a favorable trend in reducing TC and non-HDL-C from 1999 to 2011 in Tehran; however, it was limited due to the small sample size and single-district sampling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations